ANALISA PEGARUH KETIDAKPUASAN KONSUMEN , HARGA DAN IKLAN PRODUK PESAING TERHADAP KEBUTUHAN MENCARI VARIASI DAN KEPUTUSAN PERPINDAHAN MEREK PADA SHAMPOO SUNSILK DI PEKANBARU - Venny Ayu Hadriani; Alvi Furwanti Alwie; T. Firly Musfar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to analyze the effect caused by the variable Discontent Consumer Product Price and Product Ads Competitors to the Need for Variations and Trademark Transfer Decision. This study used a technique incidental Sampling with a sample of 112 people.The analytical method used in this research is descriptive method kuantiatatif, simultaneous analysis, partial analysis and path analysis using SPSS 21. From the results showed that the variables have influence significantly the price of the Need seek variety Consumer Dissatisfaction while variable and variable Competitor Product Ads no significant effect on Need for Variations and Consumer Dissatisfaction variables, Product Price and Product Ads Competitors mempuyai significant effect on the variable displacement Brand. the effect of this variable was 18.4% for the variable Needs for variety and 31% for the variable displacement Brand. The rest was influenced by other variables, namely 81.6% for Need for variety and 69% for the variable displacement Brand.As for the influence of consumer dissatisfaction and Product Ads Competitors have influence but not directly against perpindaha brand through the need to find variations while variable rates have indirect influence on Brand Switching through requirement for variation.Keyword : Disatisfction, product pricing, advertising competitor products, varietyseeking and brand switching